The psychological sequelae of involvement in combat: a preliminary investigation - Hodgson, Shane Ralph Colin (Rhodes University, Faculty of Humanities, Department of Psychology, 1992)
The psychological sequelae of being involved in combat are only recently coming to be understood. Most of the available data are from research conducted on help-seeking Vietnam veterans in the United States, and very little work has been done in South Africa. There does not as yet appear to be any instrument designed specifically to detect combat-related psychopathologies amongst soldiers who are still in active service, either in the USA or in South Africa. Combat involvement has been shown to lead to a high incidence of combat stress reaction. This in turn has shown that it can predispose sufferers to the development of a Post-traumatic Stress Disorder. It is thus expected that there would be significantly higher incidences of reported symptoms of stress disorders amongst soldiers exposed to high levels of combat as compared with a similar group of soldiers who had no combat involvement. This study used a self-reporting questionnaire, developed in the USA but adapted for use in South Africa, to allow the soldiers in the study to rate the severity of various symptoms derived from the DSM-III criteria for Post-traumatic Stress Disorder. A Beck Depression Inventory was also administered to eliminate any persons who nay have been exhibiting symptoms of depression, as this would have confounded the results. Both questionnaires were administered to serving members of the Permanent Force of the South African Defence Force, with one group being members of various high-combat units based in what was then South West Africa, and the other group being non-combat or Headquarters elements. As a precondition of the study, absolute confidentiality of the respondents and their units was maintained. The study found the expected higher scores in the high-combat group, and also showed that the Keane questionnaire has a good coefficient alpha in South Africa. The study closes with several recommendations for further research, especially in the light of the new PTSD criteria in the DSM-IIIR.
Keywords: War -- Psychological aspects; War victims -- Mental health; Post-traumatic stress disorder